MODEL KAJI TINDAK PROGRAM PEMBANGUNAN PARTISIPATIF PENGENTASAN KEMISKINAN DAN RAWAN PANGAN - P. Eko Prasetyo; Marimin Marimin; Adang Samsudin S. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
The objective of the article was to explain essential and urgency of the model of participative development program as an effort to maximize real potencies: economy, social, poli- tic and local culture, so that they can meet living need themselves independently and sustainability. The subjects of the study are all local poor people in Bringin rural area. Result of the research indicated that people awareness can maximize their potency that determined by the creativity and not due to the facility as government gave. The research explained that the incapable people problem was not merely due to absence of capital. However, it was due to awareness and working ethos that awakening in order to resolve the poverty problem. Therefore, in the evaluative action at least it was required four pillars, namely: job opportunity, social protection, capability improvement and people-empowering pillars. Then, evaluative action implementation of widening empowerment program based on local resource and creative economy was an essential, urgent strategy model to develop as effort of resolving poverty.